Headache With a Normal MRI - Nathaniel Schlicher; Raymond Ten Eyck (Association of American Medical Colleges, 2010)
Abstract This case involves an encounter following an outpatient MRI in a 58-year-old woman with a history of lung cancer on anticoagulation. The learner must evaluate a difficult presentation of an intracranial hemorrhage with multiple potential areas for suboptimal care due to the limitation of advanced imaging, complex medical confounders, and need for advanced critical thinking. The patient suffers an adverse outcome if diagnostic imaging is not repeated in the emergency department. The case is designed to be utilized with a high-fidelity simulator but is also amenable to case presentation and/or roundtable discussion with exhibits. Upon conclusion of the case, the scenario can be debriefed utilizing an included PowerPoint slide show. This case has not undergone formal testing for training purposes. It is available for teaching case files and simulation training based on the materials provided with the appropriate diagnostic imaging.